Validity of mannheim peritonitis index in predicting outcome of patients with perforative peritonitis in a tertiary care centre Kerala, India - Mathew, Alex; John, Joby; Sasikumar, Asha (International Journal of Research in Medical Sciences, 2019)
Background: Perforation peritonitis is one of the most commonly encountered surgical emergencies in our country. The prognosis of secondary peritonitis remains poor despite development in diagnosis and management. Early identification of patients with severe peritonitis may help in selecting patients for aggressive surgical approach. Methods: The study was conducted in 128 cases of perforation peritonitis admitted and treated in the department of surgery in a tertiary care centre. Initial diagnosis was made on the basis of detailed history, clinical examination and presence of pneumoperitoneum on erect abdominal X-ray. Patients were first assessed using a predesigned Performa, then MPI score was calculated for each patient and the patients were followed-up till death or discharge from the hospital. Results: The ROC curve analysis shows area under the curve was 0.986 with a standard error of 0.008, 95% CI (0.971 to 1.001), p<0.0001. In our study authors found that for the MPI score of 26, sensitivity was 91.3% and specificity was 92.4%, with a positive likelihood ratio of 12.01 and a negative likelihood ratio of 0.09. Age of the patient, presence of organ failure, associated malignancy, generalised type of peritonitis and the original MPI Score has got a significant association with the final outcome (i.e. p value <0.05). Conclusions: MPI is an excellent prognostic index for peritonitis with high accuracy in individual prognosis that is cheap, cost effective, easily measurable and reproducible. The study accentuates that early diagnosis, appropriate resuscitation and prompt surgical intervention still remain the keystones in the management of perforation peritonitis.